On Process Intensification through Membrane Storage Reactors - John Lowd (MDPI AG, 2021)
In this work, a dynamic, one-dimensional, first principle-based model of a novel membrane storage reactor (MSR) process is developed and simulated. The resulting governing equations are rendered dimensionless and are shown to feature two dimensionless groups that can be used to affect process performance. The novel process is shown to intensify production of a desired species through the creation of two physically distinct domains separated by a semipermeable boundary, and dynamic operation. A number of metrics are then introduced and applied to a case study on Steam Methane Reforming, for which a parametric study is carried out which establishes the superior performance of the MSR when compared to a reactor operating at steady state (SSR).